Teachers’ Competency As Correlates To Students’ Academic Performance In Mathematics - SABITU, Kamoru Abiodun (PT. Antis International Publisher, 2024)
The study examined the Impact of Teachers’ Competency on the Academic performance of Senior Secondary School Students in mathematics in Oyo State, Nigeria using Oyo metropolis as a case study. This study adopted a survey design. The population of this study involved all senior secondary school II students (SS2) in Oyo metropolis where a total of 200 students were drawn as sample. Three research questions guided the study and were answered using Pearson Product Moment Correlation Coefficient (PPMC). Self-structured and constructed validated questionnaire was used to collect data from the respondents. The findings revealed that there is a positive relationship between academic competence and students’ academic performance in mathematics among senior secondary school students in Oyo metropolis; there is a very strong relationship between professional competence and students’ academic performance in mathematics among senior secondary school students in Oyo metropolis and there is a weak significant relationship between personal competence and students’ academic performance in mathematics among senior secondary school students in Oyo metropolis. Based on the findings, it was recommended among others that teachers with good professional background as well as specialist in the field of mathematics education should be employed for teaching of the subject in schools.